2001
DOI: 10.1179/acb.2001.038
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Overdose With Trazodone : Case Report and Literature Review

Abstract: A fatal case of suicide with trazodone alone in a 40-year-old patient is reported. Life-threatening arrhythmias, such as torsades de pointes and complete AV block, are recorded. Blood collected at admission contained a trazodone toxic concentration of 25.4 micrograms/mL. The patient developed multiple organ failure and died less than 24 hours after his admission to the emergency department. The authors discuss the effects of overdose of trazodone, a well-known safe antidepressant drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 10 publications
0
35
0
1
Order By: Relevance
“…Studies on amitriptyline [4,18,28,31,33,34,54,55], carbamazepine [28,30,31,36,37], tramadol [22,46,[56][57][58][59] and trazodone [47][48][49][60][61][62][63] related deaths and PMR have frequently been reported. Propofol related deaths [64][65][66][67][68][69] have frequently been reported, but studies on PMR of propofol have not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on amitriptyline [4,18,28,31,33,34,54,55], carbamazepine [28,30,31,36,37], tramadol [22,46,[56][57][58][59] and trazodone [47][48][49][60][61][62][63] related deaths and PMR have frequently been reported. Propofol related deaths [64][65][66][67][68][69] have frequently been reported, but studies on PMR of propofol have not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…c Full line: blank hair using sodium hydroxide; dotted line, blank hair using phosphate buffer. 1, venlafaxine; 2, m-chlorophenylpiperazine; 3, desmethylfluoxetine; 4, viloxazine; 5, fluvoxamine; 6, fluoxetine; 7, fluoxetine d 6 In blood, the intrabatch and interbatch precisions were acceptable for all compounds, except for sertraline at high concentration (19%). Intrabatch precision for brain tissue samples was acceptable, except the intrabatch precision for citalopram at low concentrations (16%).…”
Section: Validationmentioning
confidence: 96%
“…These highly prescribed drugs are, however, frequently used together with other legal or illegal drugs and can result in synergy of symptoms and intoxications [1][2][3][4][5][6][7][8][9][10][11][12]. Furthermore, severe life-threatening interactions such as the serotonin syndrome have been described [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular effects of trazodone ingestion are generally minor, and include mild hypotension. A small number of fatalities have been reported, and these have involved patients who ingested massive quantities of trazodone or co-ingested other drugs, particularly selective serotonin reuptake inhibitors (4,5). Both QT prolongation and torsades de pointes are recognized complications of trazodone overdose (6,7).…”
Section: Ja Service and Ws Waringmentioning
confidence: 99%